PERSEPSI MAHASISWA TERHADAP PELAYANAN BANK SYARIAH - Annisa Afwani; Anggun Rohaya Putri Munthe; Khaila Calsa Fhadillah; Muhammad Ikhsan Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze students' perceptions of Islamic banking services using a qualitative, interview-based approach. The primary focus of the study is students' understanding of Islamic service principles, their experiences as customers and prospective customers, and the factors influencing their assessment of service quality. Data were obtained through semi-structured interviews with several students from various study programs. The results indicate that most students have positive perceptions of Islamic banking service ethics and transaction security. However, complaints persist regarding the limited digitalization of services and the lack of socialization regarding Islamic products. This study recommends optimizing education, improving digital technology, and strengthening services based on the values ​​of maqāṣid al-Shari'ah (the principles of Islamic principles).